Initial Analysis of Floating Fiber Embankment Construction: Working Principle, Material Characteristics, and Potential Applications in Coastal Areas - Sunaryo, Sunaryo; Wahyudi, Slamet Imam; Ni'am, Moh. Faiqun (Universitas Ibn Khaldun Bogor, 2025)
Sea level rise due to climate change and land subsidence in coastal areas have increased the frequency of tidal flooding, especially in Indonesia. Conventional embankments that are generally used to hold back seawater have limitations in adapting to fluctuations in water levels. This study evaluates a floating fiber embankment as an innovative solution for tidal flood mitigation. The embankment is designed to automatically adapt to changes in sea level using elastic and corrosion-resistant fiber materials. Numerical simulations based on the finite element method (FEM) were performed using ANSYS software to analyze the stress, strain, and deformation of the floating fiber embankment under hydrostatic pressure. The simulation results showed a maximum stress of 8231 x 10^6 Pa with a maximum deformation of 0.43 meters. Laboratory experiments using a 1:20 scale prototype validated the simulation results, with a maximum stress of 8210 x 10^6 Pa and a maximum deformation of 0.41 meters. The results showed that the floating fiber embankment has good adaptive capabilities in resisting hydrostatic pressure and functions automatically without requiring manual intervention. This technology has the potential to be an effective and sustainable solution for tidal flood mitigation in coastal areas, especially in areas that often experience land subsidence and sea level rise due to climate change.